The management of over closured anterior teeth due to attrition - Eha Djulaeha; Sukaedi Sukaedi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Tooth is the hardest tissue in human body, that can be injured because of attrition process. For old people, denture attrition process is caused by psysiological process relating with the mastication function which also supported by some bad habits such an bruxism, premature contact, and consuming habit of abrasive food. Attrition or abrasion can also be happened with patien’t dentition who does not have teeth subtutition for long time due the lost of their maxillary as well as mandibulary. The pasient will loose their vertical dimension of occlusion, injure, and the lower jaw becomes over closed which is called over closure. Purpose: This article reported the management of over closured anterior teeth due to attrition. Case: a seventy six year old woman patient came to Prosthodontic Clinic in Faculty of Dentistry, Airlangga University, to rehabilitate her upper and lower severe attrited anterior teeth and her posterior teeth. The patient has experienced of wearing acrylic removable mandibular partial denture ten years ago. Unfortunaly, the denture was uncomfortable, and she did not wear it anymore since five years ago. Case management: The severe attrition of anterior teeth with the lost of occlusal vertical dimension can be treated by improving the occlusal vertical dimension gradually. The treatment is then followed by the increasing of the height of the anterior teeth by lengthening the crown teeth of upper jaw with 12 units of span bridge and the acrylic removable partial denture of lower jaw. Conclusion: The severe attrition of anterior teeth with the lost of occlusal vertical dimension can be treated by improving the occlusal vertical dimension gradually, using long span bridge and acrylic removable partial denture.